Detail specification for radio frequency coaxial connectors (series SMA). 50 ohms, unsealed, soldered, centre contact, clamp outer for flexible cables, solder outer for semi-rigid cables. Control drawings. Mating face details and gauge information Part 2, (15th April 1978) - British Standards Institution,
No abstract available